Effect of precursor morphology of cellulose-based hard carbon anodes for sodium-ion batteries - Sarma, Hridip Ranjan; Sun, Ju; Gunathilaka, Isuru E.; Hora, Yvonne; Rajkhowa, Rangam; Forsyth, Maria; Byrne, Nolene (Frontiers in Batteries and Electrochemistry, 2024)
Hard carbon with different microstructures and physicochemical properties can be obtained based on the precursor used, and these properties have a direct impact on the electrochemical performance. Herein, two different precursors from a single source of waste cotton textiles have been prepared to be either cotton snippets retaining the original fiber structure of cotton or a microfibrillated cellulose, which has a very different morphology and surface area. Both the cotton snippet (CS) and the microfibrillated cellulose (MFC) have been carbonized to prepare hard carbons MFC-C and CS-C, and their electrochemical performance is evaluated in sodium-ion batteries (NIBs). Physicochemical properties in terms of a higher interlayer spacing of 3.71 Å and a high defect ratio (ID/IG) of 1.10 resulted in CS-C having a relatively higher specific capacity of 240 mAh g-1 in comparison to 199 mAh g-1 in MFC-C when cycled at 50 mA g-1. In addition, ex-situ MAS (magic angle spinning) NMR (nuclear magnetic resonance) spectroscopy on the solid electrolyte interphase (SEI) layer of CS-C revealed a lesser amount of conductive SEI layer on its surface compared to MFC-C, mainly composed of NaF and an additional FSI-derived Na complex, suggested to be Na2 [SO3-N-SO2F]). In contrast, MFC-C revealed a greater amount of SEI-related compounds, which is interpreted as a thicker SEI layer resulting in a long Na+ diffusion pathway and slower Na+ reaction kinetics. This study provides insight into the effect of microstructural differences arising from different cellulose precursors on the electrochemical performance, thereby aiding in the fabrication and optimization of hard carbon anodes for sodium-ion batteries.